2021
DOI: 10.1093/ejcts/ezab146
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis for early mortality in emergency acute type A aortic dissection surgery: experience of Tokyo Acute Aortic Super-network

Abstract: OBJECTIVES We investigated the various pre- and postoperative complications related to early (30-day) mortality after open surgery for acute type A aortic dissection. METHODS Data from the Tokyo Acute Aortic Super-network database spanning January 2015 to December 2017 were retrospectively reviewed. Pre- and postoperative factors related to early postoperative mortality were assessed in 1504 of 2058 (73.0%) consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Our study also found the correlation of rs2364723 and rs35652124 polymorphisms with incidence of organ ischemia such as brain ischemia and coronary artery involvement. Recent data showed that vital organ ischemia was a risk factor for early mortality after AAAD repair [34]. These evidences suggested that NFE2L2 gene polymorphisms not only correlated with onset risk but also severity of AAAD.…”
Section: Discussionmentioning
confidence: 94%
“…Our study also found the correlation of rs2364723 and rs35652124 polymorphisms with incidence of organ ischemia such as brain ischemia and coronary artery involvement. Recent data showed that vital organ ischemia was a risk factor for early mortality after AAAD repair [34]. These evidences suggested that NFE2L2 gene polymorphisms not only correlated with onset risk but also severity of AAAD.…”
Section: Discussionmentioning
confidence: 94%
“…The Tokyo Acute Aortic Super‐Network currently consists of 39 participating hospitals with specialized care for AAD and ruptured aortic aneurysm; patients with suspected or confirmed AAD are first referred to such hospitals, as reported elsewhere. 20 , 21 Detailed data on all patients treated in their emergency departments, cardiovascular surgery departments, and cardiovascular care units were routinely recorded and submitted to the data management center on specific survey forms.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there have been several attempts to shorten the transfer time to a cardiovascular operating unit. One of the famous models is the Tokyo Acute Aortic Super-network (TAAS) [3]. TAAS was established in 2010, and covers approximately 70 participating hospitals.…”
Section: Backgroundsmentioning
confidence: 99%